2014
DOI: 10.1080/09168451.2014.905192
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of the cyclohexane fragment of enacloxins, a series of antibiotics isolated from Frateuria sp. W-315

Abstract: An efficient and good yield synthesis of the cyclohexane moiety of enacyloxins, a series of antibiotics isolated from Frateuria sp. W-315, was achieved from d-quinic acid using a successive Barton–McCombie deoxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that the same research team also reported a synthesis of this  ring from D-quinic acid in 2014, to determine the absolute configuration of this fragment. 12 However, the product obtained here is a nonprotected diol and there is no indication regarding the possibility to selectively esterify the C3′ OH position of this diol, which may pose problems in a total synthesis context.…”
Section: Paper Synthesismentioning
confidence: 94%
“…It is worth mentioning that the same research team also reported a synthesis of this  ring from D-quinic acid in 2014, to determine the absolute configuration of this fragment. 12 However, the product obtained here is a nonprotected diol and there is no indication regarding the possibility to selectively esterify the C3′ OH position of this diol, which may pose problems in a total synthesis context.…”
Section: Paper Synthesismentioning
confidence: 94%
“…[3][4][5][6] A new organocopper mediated coupling reaction with acid chloride was found during the synthetic studies. [7][8][9] Polynactin produced by Streptomyces actinomycetes comprises a series of unique tetrameric macrolides in which monomeric enantiomers are alternately ester-bonded. 10) Streptomyces polynactin was once used as an acaricide, but later it has been commonly applied as a immunosuppressant and an antibiotic for multidrug resistant bacteria.…”
Section: Organic Compounds Derived From Microorganismsmentioning
confidence: 99%
“…As demonstrated above, ENX-IIa piques massive and multifaceted scientific interest. Oddly enough, no member of the ENX family has ever been synthesized, despite the efforts of Kiyota’s team that reported on the synthesis of various fragments . An overall structural complexity added to the C1–C11 chloroundecapentaenoic region sensitivity are likely the primary reasons behind the absence of successful total synthesis thus far.…”
mentioning
confidence: 99%